A simulation study of the internal twisting torque in the fouetté turn - Imura, A.; Yeadon, M. R. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
The purpose of this study was to investigate the effects of the magnitude of the twisting torque for one revolution of a Fouetté turn. Simulations were performed using a simple model comprising the supporting leg and the remainder of the body. It is shown that when the dancer turns more than one revolution with a small twisting torque, the turn will be decelerated and will finally stop. A large twisting torque is required at the start of each turn in order to increase the angular momentum which will subsequently decrease during the turn due to friction.